La estimulación de las habilidades lingüísticas en el desarrollo de la comunicación y la expresión verbal en los niños y niñas de 4 a 5 años de edad, en la unidad educativa Santa Marianita de Jesús, provincia Bolívar, en el año 2022 - Gutiérrez Andrés (2022)
As is well known communication and verbal expression are the primary basis for a good integral development of students, because language is the basis by which people manage to communicate with each other, also express their ideas, thoughts, desires and feelings, for that reason I have decided to develop this project of curricular integration, with the intention of discovering new ways to stimulate language skills in children from 4 to 5 years old in the Santa Marianita de Jesus Educational Unit in Chimbo Canton, Bolivar province in the period 2021-2022. This research is aimed at seeking the improvement of both communicative and language skills, it has a structure that goes from the development of activities, study objectives, theoretical framework, to an observation sheet which will finally lead us to an evaluation of all the results obtained in the research. Likewise, within this research we will address different topics such as, for example, the stimulation of linguistic skills and its complications, types of linguistic skills, communication, among others. In addition, this research works under the mantle of a qualitative methodological approach which allows us to make a change through the application of a previous study, in which we will use an observation sheet to check if the didactic activities elaborated help the stimulation of linguistic and communicative skills in children.